Pengaruh Gender Terhadap Perilaku Etis Akuntan Di Minangkabau (Studi Eksperimentasi Semu pada Mahasiswa Akuntansi di Kota Padang) - Ridha Oktarina; Sany Dwita; Halmawati Halmawati (Wahana Riset Akuntansi, 2017)
This study aims to provide empirical evidence on: 1) The existence of holier than thou perception bias among Minangkabau male and female accountants. 2) Whether female accountants demonstrate a higher holier than thou perception bias compared to their male counterparts. Data for this study were collected using a survey questionnaire administered to 235 accounting students in 4 universities in Padang. Independent sample T-test and ANOVA were used to analyzed the data. Results of this study show the existance of the holier than thou perception bias among Minangkabau male and female accountants. Furthermore the result show that Minangkabau female accountants demonstrate a higher holier than thou perception bias compared to their male counterparts.Keywords: Gender, holier than thou, perception bias.